Roman Catholicism - Boettner, Loraine, 1901-1990 (Presbyterian and Reformed Pub. Co, 1962)
A comprehensive examination of traditional Roman Catholicism that compares evangelical Protestant and Roman Catholic doctrines and the role each has played in history.